The significance and scope of evolutionary developmental biology: a vision for the 21st century. Issue 3 (June 2015) - Moczek, Armin P.; Sears, Karen E.; Stollewerk, Angelika; Wittkopp, Patricia J.; Diggle, Pamela; Dworkin, Ian; Ledon‐Rettig, Cristina; Matus, David Q.; Roth, Siegfried; Abouheif, Ehab; Brown, Federico D.; Chiu, Chi‐Hua; et al.
SUMMARY Evolutionary developmental biology (evo‐devo) has undergone dramatic transformations since its emergence as a distinct discipline. This paper aims to highlight the scope, power, and future promise of evo‐devo to transform and unify diverse aspects of biology. We articulate key questions at the core of eleven biological disciplines—from Evolution, Development, Paleontology, and Neurobiology to Cellular and Molecular Biology, Quantitative Genetics, Human Diseases, Ecology, Agriculture and Science Education, and lastly, Evolutionary Developmental Biology itself—and discuss why evo‐devo is uniquely situated to substantially improve our ability to find meaningful answers to these fundamental questions. We posit that the tools, concepts, and ways of thinking developed by evo‐devo have profound potential to advance, integrate, and unify biological sciences as well as inform policy decisions and illuminate science education. We look to the next generation of evolutionary developmental biologists to help shape this process as we confront the scientific challenges of the 21st century.